Sosialisasi dan Pembinaan Kaidah Penambangan Yang Baik (Good Mine Practice) Bagi Penambang Dan Masyarakat Lingkar Tambang Batubara Di Kecamatan Lamuru Kabupaten Bone Provinsi Sulawesi Selatan - widodo sri; Sufriadin Sufriadin; Irzal Nur; Asran Ilyas; Rizki Amalia; Arga Gautama; Umar Triadi Rivai; A. Ikram Fikriawan (Faculty of Engineering UNHAS, 2023)
Community service activities UNHAS-Community Partnership Program (PPMU-PK-M) has partnered with the community and coal miners in Sengengpalie Village, Lamuru District, Bone Regency, South Sulawesi Province. The partners involved in this socialization and development are a community group called the “Mario-Mario Community Forum”. Partners involved contribute as participants and facilitators in the implementation of community service activities (PkM). This PkM activity is in the form of socializing and fostering Good Mining Practices for miners and the community around coal mines. Environmental problems and post-coal mining land conditions at community service (PkM) locations pose enormous problems and risks. These problems include the formation of acid mine drainage which is very dangerous to the environment and the lives of people and other living things around the mining area. The second problem is the opening of pits/voids that are not properly reclaimed. The Unhas PkM team on this occasion will be presented with the community and coal miners to find solutions and anticipate possible problems that will arise due to coal mining activities in the future. The solution offered is to provide guidance to miners and the community around the coal mining area to apply Good Mining Practices (GMP) so that miners and the community work together in the implementation of coal mining from the initial stage (planning) to the reclamation stage (post-work). This socialization and development of Good Mining Practice is expected to contribute to producing Good Mining Practice practices for the target audience (miners and the community) in the mining area. The post-mining land area in the service area can be managed jointly by implementing a good environmental monitoring and management plan. Thus, acid mine drainage in post-mining areas can be prevented and post-mining holes (void) can be reclaimed properly and can be used for its designation for communities in post-mining areas. The reclamation activities are directed at turning the post-mining land into rice fields, cattle and goat areas or plantation areas. The results of the quantitative analysis of the pre-test and post-test showed that there was an increase in the knowledge/understanding of the participants by 43% to know/understand and 37% to really know/understand Good Mining Practice. The increase in the percentage of respondents' knowledge shows that the implementation of this community service activity can be said to have reached the target, namely coal miners and the community have understood and understood GMP or Good Mining Practice.